Bacterial endotoxins - Weinbaum, G. (Microbial toxins, 1971)
Microbial Toxins, Volume IV: Bacterial Endotoxins covers a general introduction of bacterial endotoxins, as well as research concerning structure (both morphological and physical), chemistry, immunology, biosynthesis, and genetics of bacterial endotoxins. The book describes the general characteristics of bacterial endotoxins; the anatomy and chemistry of Gram-negative cell envelopes; and the physical structure of bacterial lipopolysaccharides. The text also discusses the isolation and chemical and immunological characterization of bacterial lipopolysaccharides; the chemistry of the unique carb.